Preliminary carcass and meat research results from cycle iv of the cattle germ plasm evaluation program - Cundiff, L.V.; Koch, R.M.; Gregory, K.E.; Crouse, J.D.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Preliminary data representing two of five calf crops in Cycle IV of the Germ Plasm Evaluation Program are reported. Carcass and meat data from 454 steers produced by mating 11 sire breeds to Hereford and Angus dams were obtained. Hereford (H) and Angus (A) sires born in the late 1960's (original) and also 1982 to 1984 (new) were compared. Steers sired by the new sample of H and A sires were heavier at slaughter than those of original sires, whereas marbling and percentages of trimmed retail product (% TRP) have not changed. HA and AH had lower % TRP than most crosses. Longhorn crosses were lightest of all crosses and were average for % TRP and % Choice. Shorthorn crosses were similar to new HA and AH in % TRP and had a higher % Choice than all crosses. Piedmontese crosses were lighter and dressed higher than new HA and AH. A low percentage graded Choice, but they excelled in muscling, trimness, and % TRP. Steaks from Piedmontese crosses were more tender than those from most breeds. Salers crosses had similar weights, less fat, larger ribeyes, and higher % TRP than new HA and AH, but a lower % Choice. Ne110re crosses excelled in dressing percentage but had the least tender steaks. Breeds differed significantly in slaughter and carcass weights, dressing percentages, carcass composition, marbling, and meat tenderness. Breeds did not rank the same for marbling as they did for tenderness.
Keywords: Beef; Breeds; Performance; Carcass traits; Tenderness; Meat